Mass spectrometry analysis of auxiliary energy-induced terpenes extraction from Andrographis Paniculata - Chia, Vi Vien; Pang, Sook Fun; Jolius, Gimbun (Elsevier Ltd, 2020)
The auxiliary energy level affects the yield of terpene extraction from Andrographis paniculata. This paper presents the effect of auxiliary energy (0.22–50 W/mL) to the extraction yield of terpenes from Andrographis paniculata for the first time. Ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS) method was developed for qualitative and quantitative analysis of terpene. It was found that, the highest yield of andrographolide (20.10 mg g/DW) and neoandrographolide (9.54 mg g/DW) was produced at a relatively lower level of auxiliary energy (1.34 W/mL). Meanwhile the highest yield of 14-deoxy-11,12-didehydroandrographolide (6.47 mg g/DW) was obtained at a higher level of auxiliary energy (25 W/mL), which indicates the existence of a thermally-induced extractive-synthesis mechanism. Principal component analyses on the mass spectra confirmed maceration, ultrasonic, and microwave assisted extraction differ appreciably and eight compounds contributing to the differences were successfully elucidated.